2019
DOI: 10.1136/bmjopen-2018-024764
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics and factors associated with post-exposure prophylaxis (PEP) treatment of dog and cat bites among left-behind children: a cross-sectional study in two cities of China

Abstract: ObjectiveAnimal injury is a significant cause of morbidity and mortality worldwide. Dog bites account for tens of millions of injuries annually and the highest risk is among children. However, children may not receive postexposure prophylaxis (PEP) treatment timely and appropriately after rabies exposure. This study aimed to investigate the characteristics and factors associated with PEP treatment of dog and cat bites among left-behind children.DesignA cross-sectional study using questionnaire was conducted in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 26 publications
1
11
0
Order By: Relevance
“…In our study, the upper extremities were more involved than the lower extremities, and this difference was significant by the post hoc test. This finding is in line with the results of Shuzhen et al (2018) study in Shenzhen and Shantou cities in China and also Zohrevandi et al (2012) in Guilan, Northern Iran [23,33]. However, some studies reported lower extremities as the most common affected site [8,26,27,30,34].…”
Section: Discussionsupporting
confidence: 87%
“…In our study, the upper extremities were more involved than the lower extremities, and this difference was significant by the post hoc test. This finding is in line with the results of Shuzhen et al (2018) study in Shenzhen and Shantou cities in China and also Zohrevandi et al (2012) in Guilan, Northern Iran [23,33]. However, some studies reported lower extremities as the most common affected site [8,26,27,30,34].…”
Section: Discussionsupporting
confidence: 87%
“…To describe responses to dog bite incidents, we used categorical values: sought healthcare and did not seek healthcare. We ran univariable and multivariable logistic regression to test variables previously found to be associated with seeking healthcare 27,28,35-37 38-42 . Based on our univariable analysis, the following covariates were used to build the model: amount of time living in the house, whether the bite was from the participant’s own dog, distance to closest healthcare facility, gender of the participant, and educational attainment.…”
Section: Methodsmentioning
confidence: 99%
“…Nearly 1 million people potentially exposed to rabies received PEP treatment annually just in the Americas 25 . However, dog bite victims typically neglect treating their wounds appropriately, if at all, and many fail to seek medical treatment 26 27 28 29 . In addition to the number of infected dogs, lack of access to appropriate medical treatment for rabies can also increase the risk of human rabies.…”
Section: Introductionmentioning
confidence: 99%
“…Dog bites are a globally recognized public health issue in both developed and developing nations in that resulting injuries are significant sources of morbidity and mortality worldwide [ 1 ]. The impacts of dog bites can be measured in terms of their health impacts to individuals affected, economic costs of treatment and health service resources and animal welfare repercussions [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing awareness with regards to the epidemiology of animal bite injuries amongst both healthcare providers and the general community is critical to reducing their overall health burden [ 4 , 19 ]. Globally the health burden of dog bites translates into tens of millions of injuries annually, with children being the population subgroup most at risk [ 1 ]. In addition to the transmission of zoonotic diseases such as rabies, dog bites inflict disfiguring injuries often requiring reconstructive surgery, cause disfigurement, disability, infection, death [ 3 , 20 , 21 ], and can have lasting psychological effects [ 10 , 12 , [22] , [23] , [24] ].…”
Section: Introductionmentioning
confidence: 99%